Unveiling the anti-inflammatory potential of olive leaf phenolic extracts in diabetes-related endothelial dysfunction - Cappellacci, Ilaria; Di Pietrantonio, Nadia; Viola, Davide; Formoso, Gloria; Zujko, Małgorzata Elżbieta; Martín-García, Beatriz; Gomez-Caravaca, Ana M.; Verardo, Vito; Pandolfi, Assunta; Pipino, Caterina (Frontiers in Endocrinology, 2025)
IntroductionDiabetes mellitus is a severe metabolic disorder strongly linked to vascular complications driven by endothelial dysfunction, chronic inflammation, and oxidative stress. Novel strategies to mitigate endothelial activation are urgently needed. In this context, phenolic compounds derived from olive leaves, a byproduct of olive oil production, have shown promising potential in counteracting diabetes- associated endothelial inflammation. This study investigates the potential anti-inflammatory effect of polyphenol-rich extracts derived from two olive leaves Spanish monocultivars, Picual and Changlot Real, in human umbilical vein endothelial cells from healthy pregnancies (C-HUVEC) and gestational diabetes (GD-HUVEC), which serve as a relevant in vitro model of hyperglycemia-induced endothelial dysfunction.MethodsOlive leaf extracts were characterized by HPLC-ESI-TOF-MS. C-HUVEC and GD-HUVEC were treated with the extracts, and pro-inflammatory markers expression (NF-kB p65, MCP-1, and VCAM-1), NF-kB p65 phosphorylation, and monocyte adhesion were assessed under basal and TNFα-stimulated conditions using RT-PCR, flow cytometry, and adhesion assays.ResultsBoth Picual and Changlot Real extracts showed no cytotoxicity at concentrations up to 50 mg/mL. Treatment with 10 mg/mL of both extracts significantly reduced NF-kB p65 and MCP-1 gene expression, as well as NF-kB p65 phosphorylation, particularly in GD-HUVEC. VCAM-1 protein expression and TNFα-induced monocyte adhesion were also significantly decreased following extract treatment. Notably, Changlot Real exhibited a broader anti-inflammatory effect across both cell types, while Picual exerted a more selective effect in GD-HUVEC.DiscussionThese findings support the anti-inflammatory activity of olive leaf polyphenols and highlight the potential of Changlot Real and Picual extracts in mitigating endothelial dysfunction associated with diabetes. By modulating the NF-kB–VCAM-1 axis, these compounds may attenuate endothelial activation, warranting further investigation into their possible role in the prevention or mitigation of diabetes-related vascular complications.